Targeted Next-Generation Sequencing Reveals Divergent Clonal Evolution in Components of Composite Pleomorphic Xanthoastrocytoma-Ganglioglioma. Issue 8 (15th June 2022) - Lucas, Calixto-Hope G; Davidson, Christian J; Alashari, Mouied; Putnam, Angelica R; Whipple, Nicholas S; Bruggers, Carol S; Mendez, Joe S; Cheshier, Samuel H; Walker, Jeffrey B; Ramani, Biswarathan; Cadwell, Cathryn R; Sullivan, Daniel V; et al.
Abstract: Composite pleomorphic xanthoastrocytoma-ganglioglioma (PXA-GG) is an extremely rare central nervous system neoplasm with 2 distinct but intermingled components. Whether this tumor represents a "collision tumor" of separate neoplasms or a monoclonal neoplasm with divergent evolution is poorly understood. Clinicopathologic studies and capture-based next generation sequencing were performed on extracted DNA from all available PXA-GG at 2 medical centers. Five PXA-GG were diagnosed in 1 male and 4 female patients ranging from 13 to 25 years in age. Four arose within the cerebral hemispheres; 1 presented in the cerebellar vermis. DNA was sufficient for analysis in 4 PXA components and 3 GG components. Four paired PXA and GG components harbored BRAF p.V600E hotspot mutations. The 4 sequenced PXA components demonstrated CDKN2A homozygous deletion by sequencing with loss of p16 (protein product of CDKN2A ) expression by immunohistochemistry, which was intact in all assessed GG components. The PXA components also demonstrated more frequent copy number alterations relative to paired GG components. In one PXA-GG, shared chromosomal copy number alterations were identified in both components. Our findings support divergent evolution of the PXA and GG components from a common BRAF p.V600E-mutant precursor lesion, with additional acquisition of CDKN2A homozygous deletion in the PXA component as is typically seen in conventional PXA.